ANALISIS PRODUK WISATA DI TAMAN BUMI PERKEMAHAN DAN GRAHA WISATA PRAMUKA (BUPERTA) CIBUBUR JAKARTA - Kadek Wiweka (Jurnal Ilmiah Hospitality Management, 2015)
This article discusses how the camping park, namely Bumi Perkemahan dan Graha Wisata Pramuka (BUPERTA) plays important role into tourism development in urban area, particularly in the city of Jakarta. As common developed city, Jakarta also faces the problem of natural conservation. This research aims to identify the potencies of natural environment to become a natural tourism product, especially in terms of attraction, accessibilities, amenities, ancillaries and community involvement. Data for this study was collected through observation method to find description of the natural tourism product in BUPERTA. These data were combined with secondary data such as reports or literature related with the object of research and presented in the form of qualitative study. Furthermore, the whole information is analyzed using SWOT analysis to obtain some potential strategies which appropriate with BUPERTA’s characteristics. This study concludes that BUPERTA has some potencies to be developed as natural tourism product, such as attraction activities, strategic location, and natural resources.